Tropical dermatology: Venomous arthropods and human skin Part I. Insecta - Haddad, Vidal [UNESP]; Costa Cardoso, Joao Luiz; Lupi, Omar; Tyring, Stephen K. (Mosby-elsevier, 2012)
Although many tropical insects carry infectious diseases, cutaneous injury can occur by other mechanisms, for example erucism (envenomation by caterpillars) or lepidopterism (dermatitis from moths). Pararama is a unique form of erucism seen in workers in contact with rubber trees in the Amazon, and it is caused by Premolis larvae, resulting in progressive periarticular fibrosis, ankylosis, and the loss of articulation. Ants and aquatic insects of the Belostomatidae family can cause painful bites and stings. Anaphylactic shock and death can result from the venom of bees and wasps. Beetles can cause vesicular dermatitis via cantharidin or paederin. Myiasis results from fly larvae (maggots) feeding on live or necrotic tissue of humans or other hosts, while New World screwworm fly larvae feed only on living tissue and burrow (ie, screw) more deeply when attempts are made to remove them. Tungiasis is characterized by very pruritic and painful papules and ulcers resulting from a Tunga flea penetrating the host's skin. Dermatologists should be able to diagnose and treat the cutaneous manifestations of these tropical insects and educate their patients on prevention. (J Am Acad Dermatol 2012; 67:339.e1-14.)
Keywords: bites; envenomation; infestations; insects; stings; tropical dermatology